Program Terapi Rehabilitasi Kecemasan Pecandu Narkoba dengan Metode Sujok Di Ponpes Salafiyah Sabilul Hikmah Malang - Mayang Wulandari; Chantika Mahadini; Amal Prihatono; Willie Japaries (STIE Malangkucecwara, 2021)
Goals of service. The Community Service Program (PKM) on Drug Addicts Anxiety Rehabilitation Therapy Program with the Sujok Method at Ponpes Salafiyah Sabilul Hikmah Malang aims to optimize the role of Islamic boarding school caregivers in an effort to socialize the movement of drug-free street children by providing counseling on tips for eliminating the anxiety of drug addicts who are addicted to drug undergoing therapy at the boarding school to stop drug use. Methods The PKM implementation team conducted counseling on how to overcome anxiety using therapeutic tools, namely massage rings, providing counseling materials, giving questionnaires about massage ring therapy, donating medicine boxes, providing digital weights, providing digital blood pressure checkers used when providing health services to patients. the caregivers of the Salafiyah Sabilul Hikmah Islamic Boarding School in Malang. Results and implications. After being given counseling about the use of ring therapy, they understand how to deal with anxiety by doing self-therapy every day for 5 minutes or 3 times or more and are able to teach other friends who feel anxious.